Rekomendasi Penentuan Prioritas Sistem Informasi di BNN Kota Malang Menggunakan Metode EasyWinWin - Aziza Zuhroh Sya'bandiyah; Mochamad Chandra Saputra; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
BNN Malang is a vertical institution that has a purpose to conduct the program of Prevention, Eradication, Abuse and Illicit Circulation of Drugs or we can call it by P4GN, especially in Malang. It consists of the head, the general subsection, the prevention and empowerment section of the community, the rehabilitation section and the eradication section. Based on interview data, it is found that there are difficulties in determining the priority of information system needs in BNN Malang. This is because no experts in the field of information technology and the needs of each different section. Therefore it is necessary to conduct analysis in determining the priority needs of information systems in BNN Malang. The EasyWinWin method is used to negotiate collaboratively and prioritize. The purpose of this research is to get recommendation of information system become priority in BNN Malang to be developed or built. The result of recommendation of information system priority determination in BNN Malang as a whole is a system of reporting activity information done daily and weekly recap, which result of weekly report with extension .ppt. In addition, it generates priority recommendations of the information system in each section or subsection.